1998
DOI: 10.1161/01.atv.18.5.842
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of VCAM-1 and ICAM-1 at Atherosclerosis-Prone Sites on the Endothelium in the ApoE-Deficient Mouse

Abstract: Abstract-Focal recruitment of monocytes and lymphocytes is one of the earliest detectable cellular responses in the formation of lesions of atherosclerosis. This localized accumulation of leukocytes is a multistep process in which the endothelium remains intact and may regulate leukocyte recruitment by expressing specific adhesion molecules. To examine the relationship of adhesion molecule expression to initiation factors and the sites of lesion formation, we analyzed the expression of vascular cell adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
522
3
32

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(582 citation statements)
references
References 52 publications
25
522
3
32
Order By: Relevance
“…28 Our results are supported by a recent study that used qualitative analysis and reported increased ICAM-1 expression in apoE-deficient animals. 29 Moreover, and very significantly, observations made on human coronar- ies and carotids show ICAM-1 expression to be correlated with vascular lesions. 7 ICAM-1, as well as VCAM-1, is expressed in a flow-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…28 Our results are supported by a recent study that used qualitative analysis and reported increased ICAM-1 expression in apoE-deficient animals. 29 Moreover, and very significantly, observations made on human coronar- ies and carotids show ICAM-1 expression to be correlated with vascular lesions. 7 ICAM-1, as well as VCAM-1, is expressed in a flow-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…39 Recent qualitative and quantitative data report a significant increase in ICAM-1 expression in the ApoE-deficient mouse. 20,21 Moreover, and very significantly, observations made on human coronaries and carotids show ICAM-1 expression correlated to vascular lesions. 9 ICAM-1 as well as VCAM-1 are expressed in a flow-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…However, qualitative and quantitative increases in endothelial ICAM-1 expression in ApoE-deficient mice are observed. 20,21 Moreover, an anti-ICAM-1 monoclonal antibody in ApoE Ϫ/Ϫ mice greatly reduced the homing of monocytes to sites of atherosclerotic lesions. 22 Finally, ICAM-1 knockout in a C57BL6 fat-fed model greatly reduced the size of vascular lesions.…”
mentioning
confidence: 99%
“…Gene Therapy smooth muscle cell proliferation, 49 suppression of vascular cell adhesion molecule-1 (VCAM-1) that is involved in the recruitment of monocytes to the site of lesion development, 50 and anti-oxidant activity that prevents the formation of oxidised LDL, which is a major factor in foam cell formation. 14,51 The significant reduction in lesion development of animals treated with rAAV/apoE3 compared with those treated with rAAV/apoE2, may reflect the association of apoE2 with type III hyperlipoproteinaemia, where individuals homozygous for apoE2 are prone to developing premature atherosclerosis.…”
Section: Inhibition Ofmentioning
confidence: 99%